A Systematic Investigation of Iminosugar Click Clusters as Pharmacological Chaperones for the Treatment of Gaucher Disease. Issue 2 (20th December 2013) - Joosten, Antoine; Decroocq, Camille; de Sousa, Julien; Schneider, Jérémy P.; Etamé, Emile; Bodlenner, Anne; Butters, Terry D.; Compain, Philippe
Abstract A series of 18 mono‐ to 14‐valent iminosugars with different ligands, scaffolds, and alkyl spacer lengths have been synthesized and evaluated as inhibitors and pharmacological chaperones of β‐glucocerebrosidase (GCase). Small but significant multivalent effects in GCase inhibition have been observed for two iminosugar clusters. Our study provides strong confirmation that compounds that display the best affinity for GCase are not necessarily the best chaperones. The best chaperoning effect observed for a deprotected iminosugar cluster has been obtained with a tetravalent 1‐deoxynojirimycin (DNJ) analogue (3.3‐fold increase at 10 μM). In addition, our study provides the first evidence of the high potential of prodrugs for the development of potent pharmacological chaperones. Acetylation of a trivalent DNJ derivative, to give the corresponding acetate prodrug, leads to a pharmacological chaperone that produces higher enzyme activity increases (3.0‐fold instead of 2.4‐fold) at a cellular concentration (1 μM) reduced by one order of magnitude.